Fungsi Manajemen Dalam Produksi Siaran Dakwah - Efendy, Erwan; Fajar, M Ichsan; Masdan, Nasrun Al; Syahbana Damanik, Ibnu Alif (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This work aims to recognize the function of management in the production of proselytizing broadcasts. Starting from how to manage to the production of the proselytizing program, this exploration uses a qualitative methodology, this discussion is highlighted or focused on the grounds that this examination is subjective in nature that focuses on the orientation of the discussion. Production management is able to actualize proselytizing programs in an organized and structured manner. With the principle of program management, proselytizing broadcasts will be more effective because indirectly the programs in the broadcast can be better arranged to create a more complex understanding for the listeners. Keywords: management, production, proselytizing